Analisis Pendidikan Tauhid dalam Kitab Al-Iqtishad Fi Al-I’tiqad: Relevansinya pada Pendidikan Islam Kontemporer - Soleman Siregar; Muhammad Yunan Harahap; Charles Rangkuti (Medan Resource Center, 2026)
This study examines the concept of tawhid education in Al-Iqtishad fi al-I'tiqad by Al-Ghazali and its relevance to contemporary Islamic education, addressing a key research gap, namely the limited systematic articulation of Al-Ghazali’s rational tauhid methods as a pedagogical framework in modern contexts. The research adopts a qualitative approach with a descriptive design through library research, utilizing primary data from the main text and supported by relevant secondary literature. Data were collected through literature review and analyzed interpretively to generate conceptual insights. The findings reveal three principal methods of Al-Ghazali’s rational tauhid: (1) the demonstrative-burhani method grounded in logical reasoning, (2) the dialectical-jadali method aimed at refuting opposing views, and (3) the integrative method that harmonizes reason and revelation. These methods position tawhid education not only as a theological construct but also as an epistemological framework that fosters critical, moderate, and adaptive learners. This study contributes academically by offering a structured conceptualization of Al-Ghazali’s tauhid pedagogy and affirms its theoretical significance for advancing the development of contemporary Islamic education that is both rational and contextually responsive.